Modelling the Invariants of Academic Migration Influencing the Territory's Socio-Economic Indicators - Kuprina, Tamara Vladimirovna; Minasyan, Svetlana Mikhaelovna; Tsaturyan, Armen Mishaevich (Economy of Regions, 2019)
Currently, the migration flows, including academic migration, are increasing. The present situation requires studying both the problems of the academic migrants' adaptation in a new socio-cultural environment and the academic migration's impact on socio-economic processes. However, there are very few studies focused on the academic migration. The article aims to demonstrate the possibilities and risks of academic migration and to model its invariants influencing socio-economic indicators. We hypothesise that certain factors might accelerate the process of migrants' adaptation and influence the socio-economic indicators of the host territory. We analysed Russia's position in the systems of academic migrations and theoretical foundations concerning the definition of the concept «academic migration» and its invariants. Based on the analysis, we consider academic migration as one of the resources that positively influence socio-economic processes. In addition, we extrapolate the thesis about internationalization of the resource blocks on the education system. Academic migration can be considered as human capital in the transfer of innovative technologies both to the host country and abroad. We analyse domestic and foreign studies describing the influence of individual factors. Moreover, we highlight the conditions contributing to an increase in the share of academic (highly skilled) migration replacing a low-skilled one. For assessing the possibilities of academic migration, we apply the method of analogy and transfer the physical quantities on the social processes. Thus, we determine adiabatic invariants of migration in general and academic migration in particular. The obtained results prove our assumption about the influence of academic migration on the socio-economic processes of the host territory. We plan to focus further research at a more in-depth study of conditions that support academic migration.